The Development of Entrepreneurship Learning Model Based upon Local Potential to Increase Interest in Entrepreneurship at SMK Negeri 1 Salatiga (Journal of Economic Education, 2022)
The small number of SMK Negeri 1 Salatiga graduates who are active as entrepreneurs demonstrates the lack of an entrepreneurial spirit among SMK students. This is quite sad given the abundance of local potential, notably the water hyacinth pest. To build local potential in the vicinity of SMK Negeri 1 Salatiga, a learning model must exist that draws students. This research aimed to assess the necessity of integrating water hyacinth craft material with entrepreneurial content in the form of a learning model for students in grade 12 at SMK Negeri 1 Salatiga. and determine the efficacy of applying the local potential-based learning model approach "water hyacinth" with class 12 students of SMK Negeri 1 Salatiga. This research utilizes a research and development paradigm (Research And Development) that facilitates the efficient and successful implementation of activities., As a result of the progress in education, a learning model will be created that further improves students' comprehension and competency, which will lead to a rise in the quality of work outcomes. The process of building an entrepreneurial learning model based on local potential comprises two major stages, the first of which is the establishment of a project-based learning model (PjBL) by direct experience using water hyacinth media.Second, the creation of a learning guide that includes an entrepreneurial module based on the local potential of water hyacinth. These situations give researchers with the inspiration to design a new innovation by combining local potential-based learning models with supporting instructional materials and the Project Based Learning (PjBL) learning model.